A method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation
The described method addresses the issue of microcracking and deformation in gel casting by using specific monomers and modified powders to create a high-strength slurry, resulting in dense and hard silicon carbide ceramics with improved mechanical properties.
Patent Information
- Application Number
- CN202411087326.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Gel casting methods for silicon carbide ceramics often result in microcracks and deformation, leading to low yield and poor industrial applicability due to insufficient strength and stability of the green body.
A method involving the use of specific monomers, cross-linking agents, and modified ceramic powders to create a high-strength, low-viscosity slurry for gel casting, followed by pressureless sintering, which includes double cross-linking through physical and chemical effects to enhance the gel network structure and reduce cracking during drying.
The method produces silicon carbide ceramics with high density, hardness, and improved drying performance, minimizing deformation and enhancing the mechanical properties of the final product.
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic technology, and in particular to a method for preparing pressureless sintered silicon carbide ceramics by gel injection molding with high strength and low deformation. Background Art
[0002] Silicon carbide ceramics not only have excellent room temperature mechanical properties, such as high bending strength, excellent oxidation resistance, good corrosion resistance, high wear resistance and low friction coefficient, but also have the best high temperature mechanical properties such as strength and creep resistance among known ceramic materials. Silicon carbide ceramic materials sintered by hot pressing, pressureless sintering and hot isostatic pressing can still maintain good high temperature strength at 1600℃, and are the best high temperature strength materials among ceramic materials. Therefore, its products are widely used in the heating and heat exchange industry.
[0003] In recent years, new colloidal molding technologies such as filter press molding, gel casting molding and direct solidification injection molding and other in-situ curing methods can be used to prepare high-reliability, complex-shaped ceramic parts. Gel casting has been widely studied in the fields of porous materials, composite materials and functional materials, but it is rarely used in actual industrial production because microcracks and deformation often occur in gel casting, resulting in low yield. For this reason, it is necessary to prepare a high-strength, low-deformation gel casting blank. Summary of the invention
[0004] In order to improve the strength of a gel-casting green body and reduce the deformation of the green body, the present application provides a method for preparing pressureless sintered silicon carbide ceramics by gel-casting with high strength and low deformation.
[0005] The present application provides a method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation, which adopts the following technical scheme:
[0006] A method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation, comprising the following steps:
[0007] S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;
[0008] S2, adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry;
[0009] S3, ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain degassing slurry;
[0010] S4. Add a catalyst and an initiator to the deaerated slurry, stir and pour into a mold, and obtain a green body after forming. Dry the green body according to a drying system to obtain a dried green body, and perform pressureless sintering on the dried green body to obtain a silicon carbide ceramic product.
[0011] The slurry prepared by monomers, cross-linking agents, dispersants, suspending agents, defoaming agents, boron carbide, carbon black and modified silicon carbide powder has high solid content and low viscosity. The green body obtained after gel injection molding has high strength, which reduces the occurrence of cracks and deformation during the drying process and improves the density and hardness of silicon carbide ceramic products.
[0012] Preferably, the monomers in step S1 include acrylamide, modified sodium alginate and potassium acrylate.
[0013] By using acrylamide, modified sodium alginate and potassium acrylate as monomers, double cross-linking can be performed through physical and chemical effects to adjust the network structure of the gel, thereby improving the strength of the gel and thus improving the strength of the wet body, and reducing cracking or deformation during the drying process; acrylamide, modified sodium alginate and potassium acrylate form an interpenetrating cross-linked three-dimensional network with the cross-linking agent through free radical polymerization and ion exchange reaction. The double cross-linked structure can greatly improve the toughness and strength of the gel network, refine the pore size of the network, obtain a denser gel network, increase the network wall thickness, improve the ability to resist drying stress, improve the drying performance of the wet body, and reduce the occurrence of cracking and deformation.
[0014] Preferably, the raw materials for preparing the modified sodium alginate include sodium periodate, sodium alginate and 3-aminophthalic anhydride.
[0015] Sodium periodate can increase the aldehyde structure of sodium alginate, introduce cross-linking points on sodium alginate, enhance the connection of the gel network, and improve the strength and stability of the gel network; 3-aminophthalic anhydride is preliminarily cross-linked with sodium alginate to modify the sodium alginate. 3-aminophthalic anhydride has good complexing ability, and the amino group can provide lone pairs of electrons, so that the gel network constructed by sodium alginate and polyacrylamide can further coordinate, further improving the stability of the gel network. Sodium periodate and 3-aminophthalic anhydride synergistically modify sodium alginate, which can improve the stability and toughness of the wet blank, reduce cracking and deformation during the drying process, and thereby improve the density and hardness of silicon carbide ceramics.
[0016] Preferably, the mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride is 1.08:1:(0.8-1.2).
[0017] The modified sodium alginate prepared according to the above mass ratio has good cross-linking and reaction properties, and can improve the toughness and stability of the gel network.
[0018] Preferably, the monomers in step S1 further include 2-acrylamide-2-methylpropanesulfonic acid.
[0019] The introduction of 2-acrylamide-2-methylpropane sulfonic acid can improve the stability and toughness of the gel network. The sulfonic acid group can participate in the cross-linking reaction, increase the connectivity of the gel network, and synergize with the modified sodium alginate to form a more solid three-dimensional interpenetrating network structure, thereby improving the drying performance of the ceramic wet blank and thus improving the density and hardness of the silicon carbide ceramic product.
[0020] Preferably, the slurry in step S2 further includes modified wollastonite whiskers.
[0021] Preferably, the raw materials for preparing the modified wollastonite whiskers include wollastonite whisker bodies and citric acid.
[0022] Wollastonite whiskers have high tensile strength, which can improve the toughness and strength of ceramic wet blanks, cooperate with three-dimensional interpenetrating double network structure gel to improve the drying performance of wet blanks, and increase the density and hardness of ceramics; citric acid can modify wollastonite whiskers to improve the dispersibility of wollastonite whiskers; modified wollastonite whiskers can also reduce the firing temperature of silicon carbide ceramics, optimize the microstructure of silicon carbide ceramics, and improve the performance of ceramics.
[0023] Preferably, the raw materials for preparing the modified silicon carbide powder in step S2 include pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine.
[0024] Polyquaternary ammonium salt is adsorbed on the surface of pretreated silicon carbide ultrafine powder through physical and chemical effects, and the dispersibility and compatibility of silicon carbide powder are improved through steric hindrance and electrostatic interaction, and the agglomeration of ceramic powder is reduced, thereby increasing the solid content and stability of the slurry; through the modification treatment of dopamine, the surface of the modified silicon carbide powder has catechol groups, and the modified silicon carbide powder can interact with the gel network structure, thereby improving the dispersion performance of the modified silicon carbide powder, increasing the solid content of the ceramic slurry, reducing the viscosity of the ceramic slurry, improving the drying performance of the ceramic body, and increasing the density and hardness of the silicon carbide ceramic.
[0025] Preferably, the pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, stirring the silicon carbide dispersion to react, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion, heating the pretreated dispersion to react, centrifuging, washing, and drying to obtain pretreated silicon carbide ultrafine powder.
[0026] The silicon carbide ultrafine powder is initially washed with a dilute hydrochloric acid aqueous solution to remove impurities on the surface of the silicon carbide ultrafine powder and reduce the occurrence of self-aggregation; the initially treated silicon carbide and glacial acetic acid are mixed and heated to react. Under heating conditions, the acetic acid molecules are stably adsorbed on the surface of the powder, and the repulsion between the powders is increased through the dual effects of steric hindrance and electrostatic stabilization, thereby reducing agglomeration and facilitating subsequent further modification treatments.
[0027] Preferably, the mass ratio of the pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine is 1: (0.005-0.01): 0.02.
[0028] The modified silicon carbide powder prepared according to the above mass ratio has good dispersibility and compatibility.
[0029] In summary, the present application includes at least one of the following beneficial technical effects:
[0030] 1. The slurry prepared by monomer, cross-linking agent, dispersant, suspending agent, defoaming agent, boron carbide, carbon black and modified silicon carbide powder has high solid content and low viscosity. The green body obtained after gel injection molding has high strength, which reduces the occurrence of cracks and deformation during the drying process and improves the density and hardness of silicon carbide ceramic products.
[0031] 2. By using acrylamide, modified sodium alginate and potassium acrylate as monomers, double cross-linking can be performed through physical and chemical effects to adjust the network structure of the gel, thereby improving the strength of the gel and thus improving the strength of the wet body, and reducing cracking or deformation during the drying process; acrylamide, modified sodium alginate and potassium acrylate form an interpenetrating cross-linked three-dimensional network with the cross-linking agent through free radical polymerization and ion exchange reaction. The double cross-linked structure can greatly improve the toughness and strength of the gel network, refine the pore size of the network, obtain a denser gel network, increase the thickness of the network wall, improve the ability to resist drying stress, improve the drying performance of the wet body, and reduce the occurrence of cracking and deformation.
[0032] 3. Polyquaternary ammonium salt is adsorbed on the surface of pretreated silicon carbide ultrafine powder through physical and chemical effects, and the dispersibility and compatibility of silicon carbide powder are improved through steric hindrance and electrostatic interaction, and the agglomeration of ceramic powder is reduced, thereby increasing the solid content and stability of the slurry; through the modification treatment of dopamine, the surface of the modified silicon carbide powder has catechol groups, and the modified silicon carbide powder can interact with the gel network structure, thereby improving the dispersion performance of the modified silicon carbide powder, increasing the solid content of the ceramic slurry, reducing the viscosity of the ceramic slurry, improving the drying performance of the ceramic body, and increasing the density and hardness of the silicon carbide ceramic. DETAILED DESCRIPTION
[0033] The present application discloses a method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation. The raw materials used in the present application can be obtained from the market unless otherwise specified. The present application is further described in detail in conjunction with the embodiments below:
[0034] Raw materials description: acrylamide (CAS No.: 79-06-1), sodium alginate (CAS No.: 9005-38-3), sodium periodate (CAS No.: 7790-28-5), 3-aminophthalic anhydride (CAS No.: 90-45-9), potassium acrylate (CAS No.: 10192-85-5), 2-acrylamide-2-methylpropanesulfonic acid (CAS No.: 15214-89-8), crosslinking agent is N, N'-methylenebisacrylamide (CAS No.: 110-26-9), dispersant is C E64, purchased from Qiren Chemical, the suspending agent is sodium carboxymethyl cellulose (CAS No.: 9004-32-4), the defoaming agent is sodium dodecyl sulfate (CAS No.: 151-21-3), the polyquaternary ammonium salt model is M550, purchased from Shandong Xuguang Chemical Co., Ltd., dopamine is dopamine hydrochloride (CAS No.: 62-31-7), the catalyst is tetramethylethylenediamine (CAS No.: 110-18-9), the initiator is ammonium persulfate (CAS No.: 7727-54-0), citric acid (CAS No.: 77-92-9).
[0035] Example 1
[0036] Preparation of modified silicon carbide powder
[0037] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.
[0038] 97.56 kg of pretreated silicon carbide ultrafine powder and 0.49 kg of polyquaternary ammonium salt were mixed and dispersed in 100 L of deionized water, stirred and reacted at a speed of 300 rpm for 4 hours in a water bath at 80°C, and a precipitate was obtained after centrifugation. The precipitate was washed with deionized water to obtain preliminary modified silicon carbide; the preliminary modified silicon carbide and a dopamine Tris solution containing 1.95 kg of dopamine were mixed and dispersed in 100 L of a mixture of deionized water and ethanol with a volume ratio of 5:1, stirred and reacted at a speed of 200 rpm at 30°C for 6 hours, and the solid product obtained after centrifugation was dried in an oven at 80°C for 6 hours to obtain a dry solid product, and the dry solid product was ground and passed through an 80-mesh sieve to obtain modified silicon carbide powder.
[0039] Preparation of modified sodium alginate
[0040] 0.69 kg of sodium alginate was dissolved in 20 L of 100 ° C deionized water, cooled to obtain a sodium alginate aqueous solution, 0.75 kg of sodium periodate was dissolved in 10 L of deionized water to obtain a sodium periodate aqueous solution, the sodium periodate aqueous solution was added to the sodium alginate aqueous solution, and the addition was completed within 2 hours to obtain a sodium alginate reaction solution, the sodium alginate reaction solution was reacted at 30 ° C in the dark for 6 hours to obtain a product solution, the product solution was transferred to a 3500 Da dialysis bag for 24 hours, the water was changed every 8 hours, and the dialyzed product solution was freeze-dried at -20 ° C to obtain aldehyde-modified sodium alginate. 0.56 kg of 3-aminophthalic anhydride and the above-prepared aldehyde-modified sodium alginate were dissolved in 20 L of 5% mass content acetic acid solution, stirred at 300 rpm in a 90 ° C water bath for 5 hours, and then freeze-dried at -20 ° C to obtain modified sodium alginate.
[0041] Preparation of modified wollastonite whiskers
[0042] 5 kg of wollastonite whiskers and 0.05 kg of citric acid were dispersed in 50 L of deionized water, stirred at 300 rpm for 30 min in a 40° C. water bath, and the solid was filtered out. The solid was placed in a vacuum drying oven and dried for 4 h to obtain modified wollastonite whiskers.
[0043] Preparation of silicon carbide ceramic products
[0044] S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;
[0045] S2. Add ceramic powders to the premix in the order of boron carbide, carbon black and modified silicon carbide powder, then add modified wollastonite whiskers to the premix and stir to obtain a slurry; wherein the monomers include acrylamide, modified sodium alginate, potassium acrylate and 2-acrylamide-2-methylpropane sulfonic acid, acrylamide accounts for 0.7% of the slurry mass, modified sodium alginate accounts for 0.8% of the slurry mass, potassium acrylate accounts for 0.2% of the slurry mass, 2-acrylamide-2-methylpropane sulfonic acid accounts for 0.3% of the slurry mass, cross-linking agent accounts for 0.2% of the slurry mass, dispersant accounts for 1.2% of the slurry mass, suspending agent accounts for 0.5% of the slurry mass, defoaming agent accounts for 0.3% of the slurry mass, ceramic powder accounts for 58% of the slurry mass, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, wollastonite whiskers account for 2% of the slurry mass, and the balance is deionized water.
[0046] S3, ball milling the slurry for 12 hours at a ball milling speed of 30 rpm, degassing after ball milling, vacuum degassing for 10 minutes, and vibrating during degassing at a vibration frequency of 5 Hz to obtain a degassed slurry;
[0047] S4. Add a catalyst and an initiator to the degassed slurry, the catalyst accounting for 0.005% of the slurry mass, and the initiator accounting for 0.005% of the slurry mass. After stirring, pour it into a mold to obtain a green body after forming. Dry the green body according to the drying system in Table 1 to obtain a dried green body. Pressureless sintering is performed on the dried green body, and the temperature is increased to 2100°C at a rate of 8°C / min. Keep warm for 2h to obtain a silicon carbide ceramic product.
[0048] Table 1 Drying system of silicon carbide ceramics
[0049] Temperature ℃ 30 40 50 50 60 70 90 100 100 70 30 humidity% 75 70 60 50 40 20 0 0 0 0 0 Time 1 20 20 2 10 6 10 5 10 10 4 Example 2
[0050] Preparation of modified silicon carbide powder
[0051] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.
[0052] 97.09 kg of pretreated silicon carbide ultrafine powder and 0.97 kg of polyquaternary ammonium salt were mixed and dispersed in 100 L of deionized water, stirred and reacted at a speed of 300 rpm for 4 hours in a water bath at 80°C, and a precipitate was obtained after centrifugation. The precipitate was washed with deionized water to obtain preliminary modified silicon carbide; the preliminary modified silicon carbide and a dopamine Tris solution containing 1.94 kg of dopamine were mixed and dispersed in 100 L of a mixture of deionized water and ethanol with a volume ratio of 5:1, stirred and reacted at a speed of 200 rpm at 30°C for 6 hours, and the solid product obtained after centrifugation was dried in an oven at 80°C for 6 hours to obtain a dry solid product, and the dry solid product was ground and passed through an 80-mesh sieve to obtain modified silicon carbide powder.
[0053] Preparation of modified sodium alginate
[0054] 0.61 kg of sodium alginate was dissolved in 20 L of 100 ° C deionized water to obtain a sodium alginate aqueous solution, 0.66 kg of sodium periodate was dissolved in 10 L of deionized water to obtain a sodium periodate aqueous solution, the sodium periodate aqueous solution was added to the sodium alginate aqueous solution, and the addition was completed within 2 hours to obtain a sodium alginate reaction solution, the sodium alginate reaction solution was reacted at 30 ° C in the dark for 6 hours to obtain a product solution, the product solution was transferred to a 3500 Da dialysis bag for 24 hours, the water was changed every 8 hours, and the dialyzed product solution was freeze-dried at -20 ° C to obtain aldehyde-modified sodium alginate. 0.73 kg of 3-aminophthalic anhydride and the above-prepared aldehyde-modified sodium alginate were dissolved in 20 L of 5% mass content acetic acid solution, stirred at 300 rpm in a 90 ° C water bath for 5 hours, and then freeze-dried at -20 ° C to obtain modified sodium alginate.
[0055] Preparation of modified wollastonite whiskers
[0056] 5 kg of wollastonite whiskers and 0.05 kg of citric acid were dispersed in 50 L of deionized water, stirred at 300 rpm for 30 min in a 40° C. water bath, and the solid was filtered out. The solid was placed in a vacuum drying oven and dried for 4 h to obtain modified wollastonite whiskers.
[0057] Preparation of silicon carbide ceramic products
[0058] S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;
[0059] S2. Add ceramic powders to the premix in the order of boron carbide, carbon black and modified silicon carbide powder, then add modified wollastonite whiskers to the premix and stir to obtain a slurry; wherein the monomers include acrylamide, modified sodium alginate, potassium acrylate and 2-acrylamide-2-methylpropane sulfonic acid, acrylamide accounts for 1.6% of the slurry mass, modified sodium alginate accounts for 1.5% of the slurry mass, potassium acrylate accounts for 0.5% of the slurry mass, 2-acrylamide-2-methylpropane sulfonic acid accounts for 0.4% of the slurry mass, cross-linking agent accounts for 0.4% of the slurry mass, dispersant accounts for 1.4% of the slurry mass, suspending agent accounts for 0.7% of the slurry mass, defoaming agent accounts for 0.5% of the slurry mass, ceramic powder accounts for 62% of the slurry mass, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, wollastonite whiskers account for 3% of the slurry mass, and the balance is deionized water.
[0060] S3, ball milling the slurry for 16 hours at a ball milling speed of 50 rpm, degassing after ball milling, vacuum degassing for 10 minutes, and vibrating during degassing at a vibration frequency of 10 Hz to obtain a degassed slurry;
[0061] S4. Add a catalyst and an initiator to the degassed slurry, the catalyst accounting for 0.01% of the slurry mass, and the initiator accounting for 0.01% of the slurry mass. After stirring, pour it into a mold to obtain a green body after molding. Dry the green body according to the drying system in Table 1 to obtain a dried green body. Pressureless sintering is performed on the dried green body, and the temperature is increased to 2200°C at a rate of 12°C / min. Keep warm for 5 hours to obtain a silicon carbide ceramic product.
[0062] Example 3
[0063] Preparation of modified silicon carbide powder
[0064] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.
[0065] 97.32 kg of pretreated silicon carbide ultrafine powder and 0.73 kg of polyquaternary ammonium salt were mixed and dispersed in 100 L of deionized water, stirred and reacted at a speed of 300 rpm for 4 hours in a water bath at 80°C, and a precipitate was obtained after centrifugation. The precipitate was washed with deionized water to obtain preliminary modified silicon carbide; the preliminary modified silicon carbide and a dopamine Tris solution containing 1.95 kg of dopamine were mixed and dispersed in 100 L of a mixture of deionized water and ethanol with a volume ratio of 5:1, stirred and reacted at a speed of 200 rpm at 30°C for 6 hours, and the solid product obtained after centrifugation was dried in an oven at 80°C for 6 hours to obtain a dry solid product, and the dry solid product was ground and passed through an 80-mesh sieve to obtain modified silicon carbide powder.
[0066] Preparation of modified sodium alginate
[0067] 0.65 kg of sodium alginate was dissolved in 20 L of 100 ° C deionized water to obtain a sodium alginate aqueous solution, 0.7 kg of sodium periodate was dissolved in 10 L of deionized water to obtain a sodium periodate aqueous solution, the sodium periodate aqueous solution was added to the sodium alginate aqueous solution, and the addition was completed within 2 hours to obtain a sodium alginate reaction solution, the sodium alginate reaction solution was reacted at 30 ° C in the dark for 6 hours to obtain a product solution, the product solution was transferred to a 3500 Da dialysis bag for 24 hours, the water was changed every 8 hours, and the dialyzed product solution was freeze-dried at -20 ° C to obtain aldehyde-modified sodium alginate. 0.65 kg of 3-aminophthalic anhydride and the aldehyde-modified sodium alginate prepared above were dissolved in 20 L of 5% mass content acetic acid solution, stirred at 300 rpm in a 90 ° C water bath for 5 hours, and then freeze-dried at -20 ° C to obtain modified sodium alginate.
[0068] Preparation of modified wollastonite whiskers
[0069] 5 kg of wollastonite whiskers and 0.05 kg of citric acid were dispersed in 50 L of deionized water, stirred at 300 rpm for 30 min in a 40° C. water bath, and the solid was filtered out. The solid was placed in a vacuum drying oven and dried for 4 h to obtain modified wollastonite whiskers.
[0070] Preparation of silicon carbide ceramic products
[0071] S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;
[0072] S2, adding ceramic powders to the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and then adding modified wollastonite whiskers to the premixed liquid, stirring to obtain a slurry; wherein the monomers include acrylamide, modified sodium alginate, potassium acrylate and 2-acrylamide-2-methylpropane sulfonic acid, acrylamide accounts for 1.15% of the slurry mass, modified sodium alginate accounts for 1.15% of the slurry mass, potassium acrylate accounts for 0.35% of the slurry mass, 2-acrylamide accounts for 0.35% of the slurry mass, and 2-acrylamide accounts for 0.35% of the slurry mass. Enamide-2-methylpropanesulfonic acid accounts for 0.35% of the slurry mass, the cross-linking agent accounts for 0.3% of the slurry mass, the dispersant accounts for 1.3% of the slurry mass, the suspending agent accounts for 0.6% of the slurry mass, the defoaming agent accounts for 0.4% of the slurry mass, the ceramic powder accounts for 60% of the slurry mass, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, wollastonite whiskers account for 2.5% of the slurry mass, and the balance is deionized water.
[0073] S3, ball milling the slurry for 14 hours at a ball milling speed of 40 rpm, degassing after ball milling, vacuum degassing for 10 minutes, and vibrating during degassing at a vibration frequency of 7.5 Hz to obtain a degassed slurry;
[0074] S4. Add a catalyst and an initiator to the degassed slurry, the catalyst accounting for 0.0075% of the slurry mass, and the initiator accounting for 0.0075% of the slurry mass. After stirring, pour it into a mold to obtain a green body after molding. Dry the green body according to the drying system in Table 1 to obtain a dried green body. Pressureless sintering is performed on the dried green body, and the temperature is increased to 2150°C at a rate of 10°C / min. Keep warm for 3.5 hours to obtain a silicon carbide ceramic product.
[0075] Example 4
[0076] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of sodium periodate used is 0.81 kg, the amount of sodium alginate used is 0.75 kg, and the amount of 3-aminophthalic anhydride used is 0.44 kg.
[0077] Example 5
[0078] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of sodium periodate used is 0.6 kg, the amount of sodium alginate used is 0.56 kg, and the amount of 3-aminophthalic anhydride used is 0.84 kg.
[0079] Example 6
[0080] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, no sodium periodate is added when preparing the modified sodium alginate, and the remainder is supplemented with sodium alginate.
[0081] Example 7
[0082] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, 3-aminophthalic anhydride is not added when preparing modified sodium alginate, and the remainder is supplemented with sodium alginate.
[0083] Example 8
[0084] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, modified sodium alginate is replaced by sodium alginate.
[0085] Example 9
[0086] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that 2-acrylamide-2-methylpropanesulfonic acid is not added in Example 9.
[0087] Example 10
[0088] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the modified wollastonite whiskers are replaced by wollastonite whiskers.
[0089] Embodiment 11
[0090] Example 11 is based on Example 3, and the only difference between Example 11 and Example 3 is that modified wollastonite whiskers are not added in Example 11.
[0091] Example 12
[0092] Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, the amount of pretreated silicon carbide ultrafine powder is 97.94 kg, the amount of polyquaternary ammonium salt is 0.1 kg, and the amount of dopamine is 1.96 kg.
[0093] Embodiment 13
[0094] Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that in Example 13, the amount of pretreated silicon carbide ultrafine powder is 96.62 kg, the amount of polyquaternary ammonium salt is 1.45 kg, and the amount of dopamine is 1.93 kg.
[0095] Embodiment 14
[0096] Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that in Example 14, the pretreated silicon carbide ultrafine powder is replaced with silicon carbide ultrafine powder when preparing the modified silicon carbide powder.
[0097] Embodiment 15
[0098] Example 15 is based on Example 3. The only difference between Example 15 and Example 3 is that in Example 15, no polyquaternary ammonium salt is added when preparing the modified silicon carbide powder, and the balance is supplemented with pretreated silicon carbide ultrafine powder.
[0099] Example 16
[0100] Example 16 is based on Example 3. The only difference between Example 16 and Example 3 is that dopamine is not added when preparing the modified silicon carbide powder in Example 16, and the remainder is supplemented with pretreated silicon carbide ultrafine powder.
[0101] Comparative Example 1
[0102] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the modified silicon carbide powder is replaced with ultrafine silicon carbide powder.
[0103] Performance testing
[0104] (1) Density test: The sample was prepared into a cubic silicon carbide ceramic specimen of 100 mm*200 mm*20 mm. The density was calculated based on the volume and mass. Each sample was tested three times and the average value was taken after measurement. The results are recorded in Table 2.
[0105] (2) Select GB 16534-2009 Test method for room temperature hardness of fine ceramics as the standard, use a Vickers hardness tester to test, calculate the Vickers hardness of the sample, test each sample three times, take the average value after measurement, and record the results in Table 2.
[0106] (3) Drying performance test: Dry the wet blank and observe and record the condition of the dry blank after drying. The results are recorded in Table 2.
[0107] Table 2 Test results of density, hardness and drying performance of silicon carbide ceramics
[0108] Test results <![CDATA[Density (g / cm 3 ).]]> Hardness (GPa) Whether there is cracking or deformation after drying Example 1 3.15 25 No cracking or deformation Example 2 3.16 26 No cracking or deformation Example 3 3.16 27 No cracking or deformation Example 4 3.14 23 No cracking or deformation Example 5 3.15 24 No cracking or deformation Example 6 3.13 23 No cracking or deformation Example 7 3.13 22 No cracking or deformation Example 8 3.11 18 Slight deformation Example 9 3.13 23 No cracking or deformation Example 10 3.12 22 No cracking or deformation Embodiment 11 3.11 20 Slight deformation Example 12 3.12 22 No cracking or deformation Embodiment 13 3.14 24 No cracking or deformation Embodiment 14 3.12 22 No cracking or deformation Embodiment 15 3.11 20 Slight deformation Example 16 3.10 17 Slight deformation Comparative Example 1 3.07 15 Deformation
[0109] From Table 2, we can see that the density is greater than 3.15g / cm 3 , the hardness is greater than 25 GPa, and there is no cracking in the green body after drying, which shows that the silicon carbide ceramic product prepared in this application has high density, high hardness and good drying performance.
[0110] As can be seen from Table 2, the only difference between Examples 4 and 5 and Example 3 is that the mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride in Example 4 is 1.08:1:0.6, and the mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride in Example 5 is 1.08:1:1.5. Compared with Example 3, the drying performance, density and hardness of Examples 4 and 5 are all reduced; this is because the amount of sodium periodate, sodium alginate and 3-aminophthalic anhydride is changed, too much or too little 3-aminophthalic anhydride will affect the cross-linking performance of the modified sodium alginate, affect the structure of the three-dimensional interpenetrating double network gel, the size and number of the pores change, the pore structure deteriorates, and then affects the drying performance, and the density and hardness of the ceramic are reduced.
[0111] As can be seen from Table 2, the only difference between Examples 6, 7, and 8 and Example 3 is that: in Example 6, sodium periodate is not added when preparing the modified sodium alginate, and the balance is supplemented by sodium alginate; in Example 7, 3-aminophthalic anhydride is not added when preparing the modified sodium alginate, and the balance is supplemented by sodium alginate; in Example 8, the modified sodium alginate is replaced by sodium alginate. Compared with Example 3, Examples 6, 7, and 8 have reduced drying performance, density, and hardness; this is because the synthetic components of the modified sodium alginate are replaced, and sodium periodate or 3-aminophthalic anhydride is not used for modification, the cross-linking sites of sodium alginate are reduced, and the stability and toughness of the gel network are reduced. When it is directly replaced with sodium alginate, the toughness of the gel network is further reduced, so that the drying performance of the green body is reduced, and the density and hardness are reduced.
[0112] As can be seen from Table 2, the only difference between Example 9 and Example 3 is that 2-acrylamide-2-methylpropane sulfonic acid is not added in Example 9. Compared with Example 3, the drying performance, density and hardness of Example 9 are all reduced. This is because without adding 2-acrylamide-2-methylpropane sulfonic acid, the cross-linking sites in the gel network are reduced, the modified sodium alginate lacks the synergistic effect with 2-acrylamide-2-methylpropane sulfonic acid, and the stability and toughness of the gel network are reduced, thereby reducing the drying performance, density and hardness.
[0113] As can be seen from Table 2, the only difference between Examples 10 and 11 and Example 3 is that in Example 10, the modified wollastonite whisker is replaced by wollastonite whisker, and in Example 11, the modified wollastonite whisker is not added. Compared with Example 3, Examples 10 and 11 have reduced drying performance, density and hardness; this is because the wollastonite whisker lacks modification treatment, the dispersibility is reduced, the synergistic effect with the gel network is weakened, and the gain effect is reduced. Failure to add modified wollastonite whisker will further weaken the synergistic effect, and the drying performance and sintering performance of the ceramic body are reduced, thereby reducing the density and hardness.
[0114] As can be seen from Table 2, the only difference between Examples 12 and 13 and Example 3 is that the mass ratio of pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine in Example 12 is 1:0.001:0.02, and the mass ratio of pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine in Example 13 is 1:0.015:0.02. Compared with Example 3, the drying performance, density and hardness of Examples 12 and 13 are reduced; this is because the mass ratio of pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine is not within the specified range. Too much or too little polyquaternary ammonium salt will affect the dispersibility of the modified silicon carbide powder, reduce the solid content of the ceramic slurry, increase the slurry viscosity, and further affect the drying performance, density and hardness.
[0115] As can be seen from Table 2, the only difference between Examples 14, 15, and 16 and Example 3 is that: in Example 14, the pretreated silicon carbide ultrafine powder is replaced with silicon carbide ultrafine powder when preparing the modified silicon carbide powder, in Example 15, no polyquaternary ammonium salt is added when preparing the modified silicon carbide powder, and the balance is supplemented with pretreated silicon carbide ultrafine powder, and in Example 16, no dopamine is added when preparing the modified silicon carbide powder, and the balance is supplemented with pretreated silicon carbide ultrafine powder. Compared with Example 3, Examples 14, 15, and 16 have reduced drying performance, density, and hardness; this is because the components in the modified silicon carbide powder are changed, the silicon carbide ultrafine powder lacks modification treatment, and is prone to agglomeration during the subsequent modification treatment process, and the effect of the modification treatment is reduced; lacking the modification treatment of polyquaternary ammonium salt or dopamine, the dispersibility of the modified silicon carbide powder is reduced, and the interaction with the gel network is weakened, so that the drying performance, density, and hardness are reduced.
[0116] It can be seen from Table 2 that the only difference between Comparative Example 1 and Example 3 is that the modified silicon carbide powder is replaced with silicon carbide ultrafine powder in Comparative Example 1. Compared with Example 3, the drying performance, density and hardness of Comparative Example 1 are greatly reduced; this is because the silicon carbide ultrafine powder lacks modification treatment and is prone to agglomeration and precipitation. The interaction between the silicon carbide ultrafine powder and the gel network is also greatly weakened, the stability of the ceramic slurry is reduced, the solid content is reduced, and the viscosity is increased, so that the drying performance of the wet blank is reduced, and the hardness and density of the silicon carbide ceramic are greatly reduced.
[0117] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation, characterized in that: The following steps are involved: S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; S2, adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; S3, ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain degassing slurry; S4, adding a catalyst and an initiator to the deaerated slurry, stirring and pouring into a mold, to obtain a green body after forming, drying the green body according to a drying system to obtain a dried green body, and pressurelessly sintering the dried green body to obtain a silicon carbide ceramic product; The monomers in step S1 include acrylamide, modified sodium alginate and potassium acrylate; The raw materials for preparing the modified sodium alginate include sodium periodate, sodium alginate and 3-aminophthalic anhydride; The mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride is 1.08:1:(0.8-1.2); The monomers in step S1 also include 2-acrylamide-2-methylpropanesulfonic acid; The slurry in step S2 further includes modified wollastonite whiskers; The acrylamide accounts for 0.7% of the mass of the slurry, the modified sodium alginate accounts for 0.8% of the mass of the slurry, the potassium acrylate accounts for 0.2% of the mass of the slurry, the 2-acrylamide-2-methylpropane sulfonic acid accounts for 0.3% of the mass of the slurry, the cross-linking agent accounts for 0.2% of the mass of the slurry, the dispersant accounts for 1.2% of the mass of the slurry, the suspending agent accounts for 0.5% of the mass of the slurry, the defoaming agent accounts for 0.3% of the mass of the slurry, the ceramic powder accounts for 58% of the mass of the slurry, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, the wollastonite whisker accounts for 2% of the mass of the slurry, and the balance is deionized water; The raw materials for preparing the modified wollastonite whisker include wollastonite whisker body and citric acid; The raw materials for preparing the modified silicon carbide powder in step S2 include pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine; The pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion liquid, stirring the silicon carbide dispersion liquid for reaction, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion liquid, heating the pretreated dispersion liquid for reaction, centrifuging, washing, and drying to obtain the pretreated silicon carbide ultrafine powder; The mass ratio of the pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine is 1: (0.005-0.01): 0.
02.
2. A method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation, characterized in that: The following steps are involved: S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; S2, adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; S3, ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain degassing slurry; S4, adding a catalyst and an initiator to the deaerated slurry, stirring and pouring into a mold, to obtain a green body after forming, drying the green body according to a drying system to obtain a dried green body, and pressurelessly sintering the dried green body to obtain a silicon carbide ceramic product; The monomers in step S1 include acrylamide, modified sodium alginate and potassium acrylate; The raw materials for preparing the modified sodium alginate include sodium periodate, sodium alginate and 3-aminophthalic anhydride; The mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride is 1.08:1:(0.8-1.2); The monomers in step S1 also include 2-acrylamide-2-methylpropanesulfonic acid; The slurry in step S2 further includes modified wollastonite whiskers; The acrylamide accounts for 1.6% of the mass of the slurry, the modified sodium alginate accounts for 1.5% of the mass of the slurry, the potassium acrylate accounts for 0.5% of the mass of the slurry, the 2-acrylamide-2-methylpropane sulfonic acid accounts for 0.4% of the mass of the slurry, the cross-linking agent accounts for 0.4% of the mass of the slurry, the dispersant accounts for 1.4% of the mass of the slurry, the suspending agent accounts for 0.7% of the mass of the slurry, the defoaming agent accounts for 0.5% of the mass of the slurry, the ceramic powder accounts for 62% of the mass of the slurry, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, the wollastonite whisker accounts for 3% of the mass of the slurry, and the balance is deionized water; The raw materials for preparing the modified wollastonite whisker include wollastonite whisker body and citric acid; The raw materials for preparing the modified silicon carbide powder in step S2 include pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine; The pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion liquid, stirring the silicon carbide dispersion liquid for reaction, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion liquid, heating the pretreated dispersion liquid for reaction, centrifuging, washing, and drying to obtain the pretreated silicon carbide ultrafine powder; The mass ratio of the pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine is 1: (0.005-0.01): 0.
02.
3. A method for preparing pressureless sintered silicon carbide ceramics by gel casting with high strength and low deformation, characterized in that: The following steps are involved: S1. Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; S2, adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; S3, ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain degassing slurry; S4, adding a catalyst and an initiator to the deaerated slurry, stirring and pouring into a mold, to obtain a green body after forming, drying the green body according to a drying system to obtain a dried green body, and pressurelessly sintering the dried green body to obtain a silicon carbide ceramic product; The monomers in step S1 include acrylamide, modified sodium alginate and potassium acrylate; The raw materials for preparing the modified sodium alginate include sodium periodate, sodium alginate and 3-aminophthalic anhydride; The mass ratio of sodium periodate, sodium alginate and 3-aminophthalic anhydride is 1.08:1:(0.8-1.2); The monomers in step S1 also include 2-acrylamide-2-methylpropanesulfonic acid; The slurry in step S2 further includes modified wollastonite whiskers; The acrylamide accounts for 1.15% of the mass of the slurry, the modified sodium alginate accounts for 1.15% of the mass of the slurry, the potassium acrylate accounts for 0.35% of the mass of the slurry, the 2-acrylamide-2-methylpropane sulfonic acid accounts for 0.35% of the mass of the slurry, the cross-linking agent accounts for 0.3% of the mass of the slurry, the dispersant accounts for 1.3% of the mass of the slurry, the suspending agent accounts for 0.6% of the mass of the slurry, the defoaming agent accounts for 0.4% of the mass of the slurry, the ceramic powder accounts for 60% of the mass of the slurry, the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, the wollastonite whisker accounts for 2.5% of the mass of the slurry, and the balance is deionized water; The raw materials for preparing the modified wollastonite whisker include wollastonite whisker body and citric acid; The raw materials for preparing the modified silicon carbide powder in step S2 include pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine; The pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion liquid, stirring the silicon carbide dispersion liquid for reaction, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion liquid, heating the pretreated dispersion liquid for reaction, centrifuging, washing, and drying to obtain the pretreated silicon carbide ultrafine powder; The mass ratio of the pretreated silicon carbide ultrafine powder, polyquaternary ammonium salt and dopamine is 1: (0.005-0.01): 0.02.
